Pemanfaatan Media Google Classroom Dalam Meningkatkan Mutu Pembelajaran Pada Masa Pandemi Covid-19 Di IHDN Denpasar - Wulandari, Ida Ayu Gde (Jurnal Penjaminan Mutu, 2021)
The use of online media as a learning medium is so familiar. Utilization of media in the midst of a global pandemic is the main choice to overcome social and physical distancing at this time. Demands in the world of education to be able to adapt to technological developments in addition to aiming to support the smooth course, also aims to streamline learning, in accordance with learning anywhere and anytime. Various forms of Learning Management System (LMS) that exist today, online learning media such as Google classroom in lectures are very commonly used by lecturers to support learning outcomes, through the features they have. Collecting data is using quantitative descriptive by using google form which are 108 respond by spreading online to Religion Education students. The purpose of this paper is to determine the use of google classroom in lectures and to find out the advantages and disadvantages of using google classroom media. Based on the results of the distribution of questionnaires to students majoring in religious education, it shows that more than 90% of students are accustomed to using google classroom with the benefits they have. In addition, some weaknesses are also felt by students during the learning process using only google classroom media.